2015
DOI: 10.1007/s11418-015-0913-9
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive and anti-inflammatory effects of myricetin 3-O-β-galactoside isolated from Davilla elliptica: involvement of the nitrergic system

Abstract: We aimed to study the antinociceptive effects of myricetin 3-O-β-galactoside (Mi), a substance isolated from the hydroalcoholic extract of Davilla elliptica. This study examined male Swiss mice, inducible nitric oxide synthase C57B16/J knockout mice (iNOS(-/-)), and their corresponding wild type (WT). Formalin and tail-flick tests were used to evaluate the nociceptive threshold, and the carrageenan-induced paw edema test was used as a model for inflammation. The following drugs were administered to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The main purpose of this study was to evaluate the effect of myricetin on atherosclerotic development using Ldlr −/− mice. Myricetin is a narurally occuring flavonoid and the anti-inflammation effect of myricetin has well been established [19, 20]. However, the efficacy of myricetin on atherogenesis and the mechanism ramained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…The main purpose of this study was to evaluate the effect of myricetin on atherosclerotic development using Ldlr −/− mice. Myricetin is a narurally occuring flavonoid and the anti-inflammation effect of myricetin has well been established [19, 20]. However, the efficacy of myricetin on atherogenesis and the mechanism ramained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…This decline of intracellular calcium hindering the release of neurotransmitters especially substance P, which are responsible for central analgesic effect. It was concluded that the anti-inflammatory and antinociceptive effects of myricetin could be imputable to the inhibition of iNOS (de Oliveira Azevedo et al, 2015). Mouse bone marrow (LPS-stimulated)-derived dendritic cells (DCs) treated with 10 µg/ml myricetin resulted in a significant reduction in TNFα secretion, IL-12 and IL-6.…”
Section: Anti-inflammatory Effectsmentioning
confidence: 99%
“…This decline of intracellular calcium hindering the release of neurotransmitters especially substance P, which are responsible for central analgesic effect. It was concluded that the anti‐inflammatory and antinociceptive effects of myricetin could be imputable to the inhibition of iNOS (de Oliveira Azevedo et al., 2015 ).…”
Section: Health Propertiesmentioning
confidence: 99%
“…Myricetin 3-galactoside (5) and myricetin 3-rhamnoside (7) have shown in vitro antioxidant and antigenotoxic activity [22,23]. In addition, myricetin 3-galactoside (5) has demonstrated antinociceptive, anticatabolic and anti-inflammatory activities [24,25]. Recently, this compound has exhibited anti-osteoporotic properties [26].…”
Section: Potential Pharmacological Activities and Clinical Studiesmentioning
confidence: 99%